1991
DOI: 10.1039/c39910001253
|View full text |Cite
|
Sign up to set email alerts
|

New rhodium complexes anchored on modified USY zeolites. A remarkable effect of the support on the enantioselectivity of catalytic hydrogenation of prochiral alkenes

Abstract: Rh-complexes with N-based chiral ligands, when anchored on a modified USY-zeolite which contains profuse supermicropores, produce a remarkable increase of enantioselectivity ( ~9 5 % )in the hydrogenation of N-acyldehydrophenylalanine derivatives and represent a truly heterogeneous counterpart of the homogeneous organometallic catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(59 citation statements)
references
References 9 publications
(2 reference statements)
1
58
0
Order By: Relevance
“…However this effect was not ascribed to a surface effect, but to 15 a change in the coordinating ability of the anion. It was observed that the substitution of triflate by a less coordinating anion, SbF 6 − or ClO 4 − , produces the same reversal in solution due to a change in the geometry, from octahedral with the coordinating anion to tetrahedral with the non-coordinating 20 one. The hydrogen bonds between silanols and triflates might be responsible for this change in coordinating character on the solid support.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…However this effect was not ascribed to a surface effect, but to 15 a change in the coordinating ability of the anion. It was observed that the substitution of triflate by a less coordinating anion, SbF 6 − or ClO 4 − , produces the same reversal in solution due to a change in the geometry, from octahedral with the coordinating anion to tetrahedral with the non-coordinating 20 one. The hydrogen bonds between silanols and triflates might be responsible for this change in coordinating character on the solid support.…”
mentioning
confidence: 98%
“…In spite of the non-crystalline character of clays, probably the most documented confinement effect on enantioselectivity is the surface effect of clay-supported chiral catalysts. In this case we can consider the surface around the catalytic complex 20 as a bidimensional nanoreactor, able to condition the approach of the reagents and thus the relative energies of the transition states. Why surface and not interlamellar space?…”
Section: Hydrogen Bondsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the abundance of chirality in nature, the discovery of a zeolite or zeolite-like microporous material with enantioselective properties has remained elusive. Enantioenriched, chiral zeolitic materials are of particular interest for their potential to provide robust, new, enantiospecific, shape-selective catalytic pathways and separation processes (6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%